Clinical and subclinical characteristics in women who have cesarean section due to placenta previa at Thai Binh Obstetrics and Gynecology Hospital (Vietnam Journal of Community Medicine, 2021)
The study was conducted on 123 patients who had to undergo cesarean section due to placenta previa at Thai Binh Obstetrics and Gynecology Hospital from June 1, 2019 to the end of May 31, 2020. The results: The rate of cesarean section due to placenta previa in the total number of cesarean section was 1.26%. Bleeding is the most common sign in placenta previa accounting for 63.4%. The rate of recurrent bleeding (more than 1 time) is common in uncentralized placenta previa, accounting for 36.4%. The most common pregnancy age is ≥ 35, accounting for 39%. The rate of correct diagnosis of placenta previa by ultrasound was 85.4%. Placenta previa clinging to the back of uterus account for 69.1%. Preoperative anemia rate of moderate and mild was 19.5%.
Keywords: Placenta previa, complications after birth.